Factors influencing the compensat[i]on levels of land grant university extension educators - Alexander, Paige Adell (Kansas State University, 2007)
This study was influenced by the desire to better understand the factors that influence the salary County Extension Agents in Kansas who are employed by K-State Research and Extension. The purpose of the study was to determine factors or the correlation among factors that influence salary compensation. Information was retrieved regarding the 241 County Extension Agents employed in Kansas. Demographic data was compiled on the Extension Agents as well as the ten factors that could influence their salary compensation. The factors are as follows: 1. area within the state; 2. county population; 3. number of agents in the county; 4. director responsibilities; 5. gender; 6. months of Extension employment; 7. years of equivalent service outside of Kansas Extension; 8. change of county employment within Kansas Extension; 9. position type; and 10. level of education. Variable selection through backward elimination was performed identifying area, population, the number of Extension Agents in a county/district, whether the Extension Agent was a director, previous years of experience in an equivalent position outside of K-State Research and Extension, whether an Extension Agent was employed by K-State Research and Extension prior to their current position, months of experience in their current position with K-State Research and Extension, and whether an Extension Agent has a Master's degree and if that Master's degree was obtained prior to the start of their current position to be the most significant influences on salary. Multiple regressions of the data were then performed to determine the significant relationships among certain variables. The population-position-gender correlation was found to be significant as well as the correlation among position types and genders. Recommendations for further research were given including studying the affect of performance evaluations and cost of living on salary compensation. In addition, recommendations for further practices include an annual review of the salary gap among position types and gender to ensure equity of salary compensation. Furthermore, recommendations were given regarding the dispersion of the level of education and timeliness of completing a Master's degree salary compensation data.
Keywords: Salary; Population; Gender; Research and Extension; Years of Experience; Education; Economics, Agricultural (0503); Education, Adult and Continuing (0516); Education, Agricultural (0517)